Indicators of the publishing process in Revista de Física Médica review (Revista de Física Médica, 2011)
The Revista de Física Médica was first published eleven years ago and numerous improvements in its publishing process have been introduced since then. The aim of this study is to perform a benchmarking of this process. Data were collected since 2004 and grouped in two intervals. Rejection rate, distribution of received originals among different areas, number of reviewers, reviewer time response, acceptance time and publishing time have been analyzed. The indicators show an improvement in the publishing process but the present quality goals have not been reached yet. The number of received manuscripts is the main limit for our publication.